2021
DOI: 10.20452/pamw.16148
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of atrial fibrillation to the safety and efficacy of mechanical thrombectomy in stroke patients

Abstract: Our study demonstrated a neutral impact of AF on the safety and efficacy of mechanical thrombectomy in the ultra-acute phase of stroke (≤ 6 hours from onset). Exposure to anticoagulant therapy preceding stroke does not significantly increase the risk of symptomatic intracranial bleeding after mechanical thrombectomy, which is also true for patients with INR in the therapeutic range. We identified the crucial parameters for the functional post-stroke status in AF-related stroke patients on days 10, 30 and 90 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 36 publications
(69 reference statements)
3
23
0
Order By: Relevance
“…An additional 2 studies were identified via expert recommendation. Finally, 10 studies [14][15][16][17][18][19][20][21][22][23] with 6543 patients were determined to satisfy our inclusion criteria with the appropriate report of outcomes of interest (eFigure 1 in Supplement 1).…”
Section: Search and Screening Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An additional 2 studies were identified via expert recommendation. Finally, 10 studies [14][15][16][17][18][19][20][21][22][23] with 6543 patients were determined to satisfy our inclusion criteria with the appropriate report of outcomes of interest (eFigure 1 in Supplement 1).…”
Section: Search and Screening Resultsmentioning
confidence: 99%
“…The size of the included studies ranged from 78 patients to 4169 patients. Eight studies [14][15][16][17][19][20][21]23 included in our analysis were determined to have good quality, while 2 studies 18,22 were determined to have fair quality (eTable in Supplement 1). Patient characteristics, such as age, baseline NIHSS, use of intravenous thrombolytics, and comorbidities, are detailed in the Table.…”
Section: Study Characteristics and Risk Of Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that the incidence of HT may also be increased in patients with a diagnosis of atrial fibrillation (AF) [33,34], whereas data on sICH frequency in this group of patients is contradictory. Some authors have found AF to be associated with sICH occurrence [44], while others have not [45]. Coronary artery disease is another comorbidity that may affect post-MT HT occurrence [33].…”
Section: Haemorrhagic Transformationmentioning
confidence: 99%